A hazai fejlesztéspolitika és térszervezés kapcsolódásának változása az európai uniós csatlakozás tükrében - Kabai, Gergely; Szabó, Pál (Közép-Európai Közlemények, 2016)
There were two significant milestones in the lives of Central and Eastern European countries. One was the political, social and economic change of regime during which the former centralized system was demolished. The other was the accession to the European Union, which provided an opportunity for this macro region for convergence as well as a social, economic and regional cohesion in Europe. Both of them had a significant effect on the development policy of the countries, thus that of Hungary as well. The exclusivity of the top-down policy ceased. Nevertheless, due to the learning of democratic patterns, the lack of balance in political power and the lack of funds a kind of reflection period was characteristic of the development policy the result of which was a kind of mixture of top-down and bottom-up policy. By joining the European Union clear external rules and mechanisms of action came into effect. Significant funds became accessible that strengthened the centralization and the top-down approach in the Hungarian development policy. The regional dimensions of the development endeavours appeared in many different ways in our country, but finally the regional formations that were suitable for serving the top-down development policy strengthened. The individual areas were affected miscellaneously by the regional dimension of the development tendencies. While funds were provided by the European Union for them, the bottom-up initiatives were not sufficiently welcomed. Such an area is in many ways that of Lake Balaton, which is homogeneous as far as tourism is concerned but administratively, thus from the perspective of development policy, it is split. Due to the top-down approach as well as the strengthening of the bureaucratic development policy the role of this area in the development policy is fading. This can later have a negative effect on the valuable, unique character of the region.